Land Consolidation Considering Natural Afforestation - Malashevskyi, Mykola; Malashevska, Olena (Geomatics and Environmental Engineering, 2022)
The article highlights the problem of natural agricultural-land afforestation with insufficient forest cover of the area. The article purports to substantiate land consolidation aimed at the rationalisation of agricultural and forest land management in such conditions. The authors identify the main approaches to the issue of natural agricultural land afforestation. The afforested areas of agricultural land are suggested for redesignation as a forest resource as a result of a swap and reallotment of land plots. As an example, consolidation of available land, in the conditions of natural afforestation, has been accomplished based on a number of land masses in Chernihiv Oblast´, Ukraine. Resulting from the project implementation, better configuration and improved layout of agricultural land plots have been achieved, while the length and placement of country lanes have been optimized. The reforested agricultural areas within the specific land mass have been redesignated as a forest resource. The advantages and disadvantages of natural afforestation in land consolidation are identified in contrast to alternative approaches. The research findings can be used by territorial communities in the upgrade of land management practices, laying out and redesign of landscape parks and other nature conservation areas that include areas of business activity.